ON THE OCCURRENCE OF NEOGLOBOQUADRINA ACOSTAENSIS IN UPPER SERRAVALLIAN SEDIMENTS OF SICILY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Neogloboquadrina acostaensis, typical Tortonian taxon, was found in Upper Serravallian sediments in a core collected in the southern offshore of Sicily. Whether the FAD of this taxon is to be considered older is here questioned.
Keywords: Biostratigraphy; Serravallian; Southern Sicily; Italy.